“Stronger with breastmilk-only initiative” in 5 African countries: Case study on the implementation process and contribution to the enabling environment for breastfeeding - Michaud-Létourneau, Isabelle; Gayard, Marion; Wassef, Jacqueline; Likhite, Nathalie; Tharaney, Manisha; Kim, Sunny S.; Menon, Purnima (Elsevier, 2023)
Background: The practice of giving water before 6 mo of age is the biggest barrier to exclusive breastfeeding in West and Central Africa. To address this challenge, a regional initiative, “Stronger with Breastmilk-Only” (SWBO), was rolled out at country level in several countries of the region. Objective: We examined the implementation process of the SWBO initiative and the contribution of its advocacy component to a more supportive environment for breastfeeding policies and programs. Methods: This study was based on 2 assessments at the national level carried out in 5 countries (Burkina Faso, Chad, Democratic Republic of the Congo, Senegal, and Sierra Leone) using qualitative methods. We combined 2 evaluative approaches (contribution analysis and outcome harvesting) and applied 2 theoretical lenses (Breastfeeding Gear Model and Consolidated Framework for Implementation Research) to examine the implementation process and the enabling environment for breastfeeding. Data sources included ∼300 documents related to the initiative and 43 key informant interviews collected between early 2021 and mid-2022. Results: First, we show how a broad initiative composed of a set of combined interventions targeting multiple levels of determinants of breastfeeding was set up and implemented. All countries went through a similar pattern of activities for the implementation process. Second, we illustrate that the initiative was able to foster an enabling environment for breastfeeding. Progress was achieved notably on legislation and policies, coordination, funding, training and program delivery, and research and evaluation. Third, through a detailed contribution story of the case of Burkina Faso, we illustrate more specifically how the initiative, specifically its advocacy component, contributed to this progress. Conclusion: This study shed light on how an initiative combining a set of interventions to address determinants of breastfeeding at multiple levels can be implemented regionally and contributes to fostering an enabling environment for breastfeeding at scale.